PEMESANAN PRODUK SOUVENIR BERBASIS WEB - Gusmaliza, Debi; Sasmita, Sasmita; Setiadi, Dedi ((JITEK)Jurnal Ilmiah Teknosains, 2023)
Pagar Alam City is known as a tourist city. Apart from being rich in ancient relics in the form of megalith stones, Pagar Alam is also famous for its natural beauty. This city makes agricultural tourism a direction for developing the people's economy, one of which is a business that sells souvenirs, where tourists from inside and outside always buy souvenirs as souvenirs for relatives and friends. The problem with ordering at this shop is that it still uses a manual system so the data entered is not computerized. In this research, a web-based souvenir product ordering application will be created. The programming languages used to create this program are Php and MySQL with the help of Visual Studio Code, Adobe Photoshop and Xampp tools. The research method used is the waterfall method which has stages such as the user requirements analysis stage, system design stage, implementation stage, verification stage, and finally the maintenance stage. The final result of this research is the creation of an application that can solve data processing problems quickly, precisely and accurately which is connected to a database, making it easier to create orders and recapitulate monthly order reports quickly and at any time if needed.